Hypothyroidism induces oxidative stress and DNA damage in breast. Issue 7 (20th June 2021) - Peixoto, Milena Simões; de Vasconcelos e Souza, Andressa; Andrade, Iris Soares; de Carvalho el Giusbi, Carolina; Coelho Faria, Caroline; Hecht, Fabio; Miranda-Alves, Leandro; Ferreira, Andrea Claudia Freitas; Carvalho, Denise Pires; Fortunato, Rodrigo S
Abstract : Breast cancer and thyroid dysfunctions have been associated for decades. Although many studies suggest a biological correlation, the mechanisms linking these two pathologies have not been elucidated. Reactive oxygen species (ROS) can oxidize lipids, proteins, and DNA molecules and may promote tumor initiation. Hence, we aimed at evaluating the mammary redox balance and genomic instability in a model of experimental hypothyroidism. Female Wistar rats were treated with 0.03% methimazole for 7 or 21 days to evaluate ROS generation, antioxidant enzyme activities, and oxidative stress biomarkers, as well as genomic instability. After 7 days, lower catalase, GPX, and DUOX activities were detected in the breast of hypothyroid group compared to the control while the levels of 4-hydroxynonenal (HNE) were higher. In addition, hypothyroid group showed an increase in γH2Ax/H2Ax ratio. Twenty-one days hypothyroid group had increased catalase and SOD activities, without significant differences between groups in the levels of oxidative stress biomarkers and DNA damage. TSH-treated MCF10A cells showed a higher extracellular, intracellular, and mitochondrial ROS production. Additionally, greater DNA damage was observed in these cells, demonstrated by a higher comet tail DNA percentage and increased 53BP1 foci. Finally, we found that TSH treatment was not able to alter cell viability. The Genome Cancer Atlas (TGCA) data showed that high TSHR expression is associated with more invasive breast cancer types. In conclusion, we demonstrate that oxidative stress and DNA damage in breast are early events of experimental hypothyroidism. Moreover, high TSH levels induce oxidative stress and genomic instability in mammary cells.